Bio-hydrolysis and bio-hydrogen production from food waste by thermophilic and hyperthermophilic anaerobic process. (September 2016) - Algapani, Dalal E.; Qiao, Wei; Su, Min; di Pumpo, Francesca; Wandera, Simon M.; Adani, Fabrizio; Dong, Renjie
Highlights: Thermophilic is more advantageous than the hyperthermophilic to pretreat FW. Long-term and stable H2 production was established in thermophilic CSTR. Process kinetics of both temperatures were obtained. Rate-limiting step in pretreatments was determined. Abstract: High-temperature pretreatment plays a key role in the anaerobic digestion of food waste (FW). However, the suitable temperature is not yet determined. In this work, a long-term experiment was conducted to compare hydrolysis, acidogenesis, acetogenesis, and hydrogen production at 55 °C and 70 °C, using real FW in CSTR reactors. The results obtained indicated that acidification was the rate-limiting step at both temperatures with similar process kinetics characterizations. However, the thermophilic pretreatment was more advantageous than the hyperthermophilic with suspended solids solubilization of 47.7% and 29.5% and total VFA vs. soluble COD ratio of 15.2% and 4.9%, for thermophilic and hyperthermophilic treatment, respectively, with a hydrolytic reaction time (HRT) of 10 days and an OLR of 14 kg COD/m 3 d. Moreover, stable hydrogen yield (70.7 ml-H2 /g VSin ) and content in off gas (58.6%) was achieved at HRT 5 days, pH 5.5, and temperature of 55 °C, as opposed to 70 °C.